Increased Levels of Fermented Soy Milk Amino Acids And Effectivenes Helping Reduce Uric Acid Serum In Male White Rats - Danang Raharjo; Veranita Weri; Wardani tatiana siska (LPPM Universitas Duta Bangsa Surakarta, 2021)
Soybean is one of the most important foodstuffs for the people of Indonesia, which is consumed to meet the nutritional needs of protein. Soybeans are consumed by the public as a side dish and snack. Soy milk is a form of processed soybean. Previous research has shown that tempeh, which is a form of fermented soybean, can reduce purine levels in soybeans, and can increase nutritional value, especially amino acid content. The purpose of this study was to determine the increase in amino acid content of fermented soy milk with the help of Lactobacilus Kasei bacteria, and its effect in helping to reduce serum uric acid levels in the blood of male white rats. Fermented soy milk is made of 250 grams of soybeans and squeezed in 5 liters of water, then heated. Lactobacilus kasei is used as a battery for fermentation and 500 grams of palm sugar is used as a source of nutrition for bacteria. The test to reduce uric acid levels was carried out in vivo by giving male white rats drinking as much as 10 mL, 20 mL, 30 mL, 40 mL, 50 mL for 14 days, then taking the blood through the tail vein, then measuring the uric acid levels using the strip method. test with the GCU easy tooch tool. To increase uric acid levels in male white rats was done by induction with chicken's liver. The results of measuring the levels of amino acids in the fermentation of soy milk increased between 1-2% with the following levels: Lysine 4.7%, Histidine 2.3%, Arginine 4.9%, Asparkate 7.8%, Treonine 2.9%, Serine 2.9%, Glutamate 14.2% , Proline 3.8%, Glycine 3.7%, Alanine 2.8%, Cystine 1.6%, Valine 3.2%, Methionine 1.2%, Isoleucine 3.8%, Leucine 5.9%, Tyrosine 2.7% , Phenylalanine 3.3%. Testing of uric acid levels in the blood of male white rats after fermented soy milk with various volume series were as follows: 6.70 mg/dL ± 1.16; 5.88 mg/dL ± 0.81; 4.63 mg/dL ± 0.92; 4.18 mg/dL ± 0.71; 4.16 mg/dL ± 0.96. Based on the results of the study, it can be concluded that fermented soy milk with the help of lactobacillus kasei bacteria can increase amino acid levels ranging from 1-2%, and the provision of drinking fermented milk can help reduce blood uric acid levels in male white rats with blood uric acid levels by 4.16 mg/dL ± 0.96.